2019
DOI: 10.1155/2019/4579380
|View full text |Cite
|
Sign up to set email alerts
|

Discharge against Medical Advice (DAMA) from an Emergency Department of a Tertiary Care Hospital in Saudi Arabia

Abstract: Background The discharge against medical advice (DAMA) in the Emergency Department (ED) is an issue of great concern because it may result in adverse consequences at a later stage. The reported worldwide prevalence of DAMA ranges from 0.07 to 20% for emergency admissions. The outcomes of DAMA can have significantly damaging effects, causing possible relapses of disease, readmission, and increases in medical costs for the patient. Therefore, it is imperative to identify the predictors of DAMA in ED. Methods It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
3
12
1
Order By: Relevance
“…The descriptive characterisitics of the study participants were reported in our similar research article published in 2019 [28]. Table 2 shows multivariable and univariate analyses to assess the relationship between the length of hospital stay and demographic and Emergency Department (ED) related factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive characterisitics of the study participants were reported in our similar research article published in 2019 [28]. Table 2 shows multivariable and univariate analyses to assess the relationship between the length of hospital stay and demographic and Emergency Department (ED) related factors.…”
Section: Resultsmentioning
confidence: 99%
“…The data were extracted and entered into Microsoft Office Excel for further analysis. The sampled population was also used in a previously published study [28].…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, the rate of DAMA among children was less than among adults because children do not work and are less affected by family problems. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In previously published studies conducted in KSA, the prevalence of DAMA was 1.6% in neonatal intensive care units[ 18 ]and was 1% among adults in the emergency department (ED). [ 19 ]Although DAMA is of major importance to public health, especially for the pediatric age group, there is a dearth of information regarding the demographic factors that might be responsible for DAMA in this specific context. Therefore, it is essential to explore the risk factors of DAMA within the pediatric age group so that early intervention can be implemented to prevent unwanted consequences, i. e., higher morbidity, mortality, and health-care costs.…”
Section: Introductionmentioning
confidence: 99%
“…DAMA was more likely to occur among younger patients; this is consistent with the ndings of other studies. A study at Princess Nourah Bint Abdulrahman University assessing the demographic factors of DAMA from the ED was the rst of its kind conducted in Saudi Arabia (10). The researchers recommended conducting further studies to investigate the risk factors for DAMA.…”
mentioning
confidence: 99%